Hydroxychloroquine and Fabry Disease: Three Case Reports Examining an Unexpected Pathologic Link and a Review of the Literature. (11th July 2022) - Sen, Rouhin; Borghoff, Kathleen; Foster, Kirk W.; Radio, Stanley J.; Erickson, Alan; Hearth-Holmes, Michelene
Abstract : Background . Hydroxychloroquine is an effective and widely used treatment in multiple autoimmune connective tissue diseases that gained a lot of publicity in the coronavirus disease 2019 (COVID-19) pandemic. Our case reports are unique in that they explore the rare and sometimes overlooked effects of this drug on multiple organ systems, specifically the kidney, cardiac muscle, and skeletal muscle. We include key histologic features in images which aid in identifying and distinguishing hydroxychloroquine toxicity from mimickers. Lastly, we report the very interesting similarity in the intracellular action of hydroxychloroquine to the pathology of Fabry disease (and its associated lysosomal enzyme, α -galactosidase A). Case Presentation . We will examine the case presentations of three female Caucasian patients: a 22-year-old with lupus nephritis class V, a 72-year-old with long-standing systemic lupus erythematosus, and a 74-year-old with undifferentiated connective tissue disease. All three patients were on hydroxychloroquine therapy for varying amounts of time with histologic evidence of hydroxychloroquine toxicity that is three is present in histological samples of the kidney, the heart, and the skeletal muscle. Conclusions . Hydroxychloroquine is a very important and beneficial medication used for various autoimmune connective tissue diseases. Clinicians should be aware of the rare but sometimes serious side effects that can result from the medication, which at times can mimic manifestations of the connective tissue disease itself or Fabry disease. A thorough investigation should be performed in these cases to properly elucidate the cause followed by the appropriate targeted therapy.